2019
DOI: 10.1097/nhh.0000000000000755
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-to-Homecare Videoconference Handoff

Abstract: Transitions of care between settings and clinicians are a time of vulnerability for patients, and can result in fragmented care, medication errors, avoidable readmissions, and patient/nurse dissatisfaction. Through the use of technology and a structured face-to-face handoff, the patient and family can be engaged in the transition across settings. The purpose of this project was to determine the feasibility and effectiveness of videoconference handoffs between inpatient, case management, and home care nurses, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Our list of responsibilities and tasks is not exhaustive. Medication safety management [ 57 ], care coordination [ 58 ], overseeing patient medication self-management [ 59 , 60 ], assessing patients’ competences [ 61 ], coaching and training patients [ 62 ], discharge planning [ 63 ] and interprofessional referrals [ 64 ] are additional nursing responsibilities and tasks identified in the literature. A scoping review of research about PC by nurses would be useful to confirm the completeness of the role described or supplement with additional responsibilities and tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Our list of responsibilities and tasks is not exhaustive. Medication safety management [ 57 ], care coordination [ 58 ], overseeing patient medication self-management [ 59 , 60 ], assessing patients’ competences [ 61 ], coaching and training patients [ 62 ], discharge planning [ 63 ] and interprofessional referrals [ 64 ] are additional nursing responsibilities and tasks identified in the literature. A scoping review of research about PC by nurses would be useful to confirm the completeness of the role described or supplement with additional responsibilities and tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The CMO statements (Table 1) summarize a complex picture that demonstrates how the family, direct care provider, and organizational contexts and mechanisms interact to generate engagement outcomes for each of these three stakeholders. We found that many studies provided evidence of components of one of the CMOs (see video messaging and open access to electronic health record data to more fully engage families including those who are not physically present at the bedside (Asan et al, 2019;Kelly et al, 2019;Kirolos et al, 2020;Knight et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, risk prediction helps to control the occurrence of serious dangerous events and increase the home care safety [ 41 , 42 ]. Furthermore, provision of basic resources and equipment based on the previous predictions can play a key role in strengthening home safe care and services [ 9 ]. The available evidence supports the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Providing safe home health care depends on several factors [ 9 ]. One of these factors is the human factor, which relates to home care providers such as nurses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%